Development of the system of criteria and indicators of improvement of organizational conditions of the balanced development of the region - Dzagoyeva, Isabella T (2019)
The complexity of regional socio-ecology-economic systems, their multiaspectness in the conditions of globalization and the increasing competition demands immediate development of theoretic-methodological provisions and practical recommendations for a conclusion of subjects to a positive trajectory of sustainable development that will allow promoting all macroeconomic interests of participants.As the end result of the subsequent coherence of organizational and economic, socio-ecology-economic and other purposes of economic entities of regional economy there has to be a possibility of ensuring the balanced development of territorial subjects of the Russian Federation.The analysis of conditions which limit development of regions or in different directions influence regional economy, allow developing the perspective directions of the successful solution of problems of the balanced development of territories. Similar situation speaks about need of development of the system of criteria and indicators of improvement of organizational conditions of the balanced development of regions.